Academic Stress on Menstrual Cycle among Adolescents - Gopika K. Govind; Dr. Gayathri Devi MS (International Journal of Indian Psychȯlogy, 2022)
Menstrual cycle is a monthly set of adjustments the body makes to get ready for pregnancy is known as the menstrual cycle and uterus prepared for conception. The lining of the uterus sheds through the vagina if the released egg is not fertilized during ovulation. Academic Stress is a pressure that is brought by the fear of failing in exams, parents’ and teacher’s expectations, competition, or the feeling that students go through while doing academic tasks like studying, taking tests, completing papers, and meeting deadlines, among other things. Students of all ages, academic levels, and disciplines can experience the effects of academic stress, which can negatively influence both their physical and mental health. This Study mainly focuses to measure the influence of the Menstrual symptoms of Academic Stress among Adolescents and also to find out the differences between Academic Stress and Menstrual symptoms on the basis of demographic variables. The study was conducted by employing quantitative research methods for Conducting and gathering the samples. The results highlighted there is a significant relationship between Academic Stress and Menstrual Cycle and also a significant difference in some demographic variables. This implies that Academic Stress leads to Menstrual irregularities in Adolescents, to overcome that Adolescents can be given stress management training, Meditation, yoga etc.